INVESTIGATION OF THE PROPERTIES OF Ge1-x Snx SEMICONDUCTOR SOLID MIXING ZONE STRUCTURE - Jumaniyozova Darmonjon Ro‘Zmetovna (Journals Park Publishing, 2025)
Currently, the fields of nanoelectronics, optoelectronics and photonics are developing rapidly. In these areas, the creation of effective working materials is an important task. Traditional Si&Ge based semiconductors are not suitable for photonics because they have an indirect energy gap.